1994
DOI: 10.9746/sicetr1965.30.1505
|View full text |Cite
|
Sign up to set email alerts
|

Visual Feedback Control Based on H^|^infin; Control Theory

Abstract: This paper proposes a robust control scheme for the robotic visual feedback control. The visual feedback control system is regarded as the motion control system based on the image information obtained from the camera mounted on the robot end-point. Two ways of visual feedback control shame, namely position-based and feature-based have been proposed. The feature-based scheme uses the object image feature directly without computing the object 3D position and orientation. In this paper the plant is represented in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 5 publications
1
9
0
Order By: Relevance
“…The sequences upstream. of the first ATG in the rat and the human PARP gene [9] were compared but no overall homology was found. However, both regions contain GC-rich boxes (CCGCCCC) which are putative Spl binding sites, known to be essential for the activity of many other promoters [29,30] (Fig.…”
Section: May 1992mentioning
confidence: 99%
See 4 more Smart Citations
“…The sequences upstream. of the first ATG in the rat and the human PARP gene [9] were compared but no overall homology was found. However, both regions contain GC-rich boxes (CCGCCCC) which are putative Spl binding sites, known to be essential for the activity of many other promoters [29,30] (Fig.…”
Section: May 1992mentioning
confidence: 99%
“…It also contains many CpG dinucleotides, which are putative methylarion sites and are often involved in the tissuespecific regulation of gene expression [3 1,32J. In the human gene, Ggura et al [9] identified a 14 nucleotide region located 171 bp upstream of the first ATG which contains 10 transcription starts. This 14 nucleotide region, with only one substitution, is also found in the rat DNA downstream of the GC boxes (Fig.…”
Section: May 1992mentioning
confidence: 99%
See 3 more Smart Citations